House X at Kommos : a Minoan mansion near the sea ; Part 1: Architecture, stratigraphy, and selected finds - Shaw, Joseph W. (Prehistory monographs, 2012)
House X is by far the largest and best appointed of the Minoan houses excavated at Kommos in south-central Crete, a Minoan harbor and settlement that later became the site of a Greek sanctuary. This is a description of the stratigraphic excavation of this elite house, along with numerous architectural plans